The market oriented university : transforming higher education - Davis, John A.; Farrell, Mark A. (Cheltenham Edward Elgar Publishing Ltd., 2016)
The next decade will be transformative for the higher education sector. Government funding is decreasing. Through their marketing activities universities have created the 'student consumer.' The student consumer is prepared to shop around, compare prices and value, and once purchased expects a return on their investment. Disruptive innovations are challenging traditional forms of learning and in many cases are viewed as better alternatives to traditional learning in the classroom. Competition from private educational providers is increasing. Their cost base is lower, and their customer focus is superior. In short, universities around the world are facing a perfect storm. While experts don't expect the higher education sector to collapse under these challenges, they do believe that for some institutions the future looks bleak. If universities are to avoid closures or mergers, they will need to adopt a market-oriented approach. This timely book urges readers to view students as customers and focuses on how universities need to reinvent themselves in order to stay relevant. Striking a difference between market-oriented and marketing, the authors provide various examples of institutions around the world that are making efforts to reposition themselves. Additionally, this book delves into the issue of undervalued faculty, arguing that education practices are in desperate need of being reimagined due to the abundance of MOOCs and adaptive and experiential learning practices within universities these days. Both university and academic leaders alike, including presidents, provosts, deans, and faculty will find value in the instructional aspects of this book as they relate to their involvement with institutional advancement agendas as well as providing insight into the changing nature of higher education and the evolving definition of what an academic career now entails
1. Towards a Market Oriented University -- 2. Competition and Rankings -- 3. Delivering Student Satisfaction -- 4. Disrupting Higher Education -- 5. From Marketing to Market Orientation -- 6. Developing and Maintaining a Market-Oriented University -- 7. Understanding the Market -- 8. Developing Strategic Directions -- 9. Differentiating, Positioning and Branding the University Index
An online preview is available from amazon: https://www.amazon.com/Market-Oriented-University-Transforming-Education/dp/1781004919
​Includes bibliographical references and index
Keywords: Higher education; HIGHER EDUCATION; CURRICULUM; MARKETING; Educational change